The Internet: Source of Promise or Source of Concern? A Case Study Of Onamong Senior High School Secondary School Students In Of Four Senior High Schools In Semarang, Central Java, Indonesia - Widyastari, Dyah Anantalia; Shaluhiyah, Zahroh; Widjanarko, Bagoes (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
Background: As the Internet penetrates homes and schools, it’s now become one of the major sources of information in adolescents’ life. The amount of time adolescents spent in front of this media is likely to increase as its availability, affordability and anonymity brought generous advantages for them. Nevertheless, despite its benefits, many studies revealed that the Internet also brought very serious risks to adolescents’ sexual attitudes and behaviors. This study examined the influence of the Internet and other factors contributing to adolescents’ sexual attitudes. Methods : It was a cross-sectional study, employing a self-administered questionnaire in a semi-school setting involving 320 students in Semarang. Result : 45.9% of the adolescents had permissive sexual attitudes. Sex, peer influence, television exposure, internet exposure, and internet content were significantly correlated to adolescents’ sexual attitudes whereas living arrangements, family relations, knowledge, printed media exposure and motive of internet access were not. The likelihood of having more permissive sexual attitudes was 3.93 and 1.81 times higher among adolescents who were unable to mention any websites and those who accessed entertainment websites. Adolescents with higher internet exposure were 0.28 times less likely to have more permissive sexual attitudes. This study indicates that the Internet exposure does not form adolescents’ sexual attitudes. It was not exposure to the medium, but users’ attitudes toward it which lead them to have permissive sexual attitudes.